2009
DOI: 10.21500/20112084.864
|View full text |Cite
|
Sign up to set email alerts
|

A validation study of the double standard scale and the rape supportive attitude scale in Brazilian women

Abstract: The need to improve measurement in research of violence against women has been recognized. The purpose of this study was introduced first psychometric data of two questionnaires assessing sexist attitudes on Brazilian women: Double Standard Scale (DSS) and Rape Supportive Attitude Scale (RSAS). Both scales were administered in two women samples (N = 300; N = 500). In accordance with previous research, the findings reproduced the single-factor structure on each scale. Reliability estimation through Cronbach' s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
3
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 3 publications
3
14
3
7
Order By: Relevance
“…In the absence of a scale with evidence of reliability and validity in Chile that assesses SDS, in this study the objective was to establish evidence of validity of the DSS for its use on Chilean university students, analyzing its factorial structure, internal consistency, evidence of convergent and discriminant validity, as well as exploring the differences in the SDS according to sex. First of all, and according to the hypothesis, our findings were consistent with the unidimensional structure of the scale in the original study (Caron et al, 1993), and studies on its psychometric properties for its use in the US (Greene & Faulkner, 2005), Spain Ubillos et al, 2016), El Salvador (Sierra & Gutiérrez-Quintanilla, 2007), Brazil (Sierra et al, 2009), and Peru , although we did not observe the unanimous difficulty identified on the low discriminative capacity of item 8, the only inverse item on the DSS, by studies in Spain in its version for adolescents, El Salvador, Brazil, and Peru, nor in any other item (see Table 1). On the other hand, although items 3 and 8 reached adequate skewness and kurtosis, and corrected item-total correlations and factor loadings over .5, we observed a slight improvement in the internal consistency of the scale with its elimination.…”
Section: Discussionsupporting
confidence: 88%
“…In the absence of a scale with evidence of reliability and validity in Chile that assesses SDS, in this study the objective was to establish evidence of validity of the DSS for its use on Chilean university students, analyzing its factorial structure, internal consistency, evidence of convergent and discriminant validity, as well as exploring the differences in the SDS according to sex. First of all, and according to the hypothesis, our findings were consistent with the unidimensional structure of the scale in the original study (Caron et al, 1993), and studies on its psychometric properties for its use in the US (Greene & Faulkner, 2005), Spain Ubillos et al, 2016), El Salvador (Sierra & Gutiérrez-Quintanilla, 2007), Brazil (Sierra et al, 2009), and Peru , although we did not observe the unanimous difficulty identified on the low discriminative capacity of item 8, the only inverse item on the DSS, by studies in Spain in its version for adolescents, El Salvador, Brazil, and Peru, nor in any other item (see Table 1). On the other hand, although items 3 and 8 reached adequate skewness and kurtosis, and corrected item-total correlations and factor loadings over .5, we observed a slight improvement in the internal consistency of the scale with its elimination.…”
Section: Discussionsupporting
confidence: 88%
“…Adherence to such normative beliefs spells negative effects on sexual health (Álvarez-Muelas et al, 2020;Grose et al, 2014;Sánchez et al, 2005). Man-favorable SDS is related to favorable attitudes toward raping women (Jamshed & Kamal, 2019;Lee et al, 2010;Mittal et al, 2017;Moyano et al, 2017;Sierra, Costa et al, 2009;Wanfield, 2018), by constituting a predictor of such attitudes . It has also been associated with aggressive sexual behavior to women (Moyano et al, 2017;Russell & Oswald, 2001;Teitelman et al, 2013;Zurbriggen, 2000), by predicting male sexual coercion toward females (Sierra, Gutiérrez-Quintanilla, et al, 2009), female sexual victimization (Dunn et al, 2014;Koon-Magnin & Ruback, 2012;Lee et al, 2010;, and sexual violence recognition being more difficult (Kim et al, 2019).…”
Section: Article In Pressmentioning
confidence: 99%
“…Es conocida la relación entre sexismo y violencia del hombre hacia la mujer (véase Juarros-Basterretxea et al, 2019). Específicamente, la vertiente tradicional del DES, entendida como mayor libertad sexual para el hombre que para la mujer, se ha asociado con actitudes a favor de la violación hacia la mujer (Jamshed & Kamal, 2019;Lee et al, 2010;Mittal et al, 2017;Moyano et al, 2017;Sierra, Costa, & Ortega, 2009;Sierra et al, 2010;Wanfield, 2018). Sin embargo, el metaanálisis de Endendijk et al (2020) destacó la presencia del doble estándar sexual en relación a la victimización sexual.…”
Section: Discussionunclassified
“…Tradicionalmente, el DES asume mayor libertad sexual para el hombre que para la mujer (Álvarez-Muelas et al, 2019;Guo, 2019;Sánchez-Fuentes et al, 2020;Sierra et al, 2018). El DES que resulta favorable para el hombre se ha relacionado con agresividad sexual del hombre hacia la mujer (Moyano et al, 2017;Noriega et al, 2020;Sierra, Gutiérrez-Quintanilla et al, 2009;Teitelman et al, 2013) y con el apoyo de actitudes a favor de la violación hacia la mujer (Jamshed & Kamal, 2019;Lee et al, 2010;Mittal et al, 2017;Moyano et al, 2017;Sierra, Costa, & Ortega, 2009;Wanfield, 2018), constituyendo un predictor de las mismas (Sierra et al, 2010). El DES también se ha relacionado con la victimización sexual de la mujer (Dunn et al, 2014;Koon-Magnin & Ruback, 2012;Lee et al, 2010;Sierra et al, 2010) y una mayor dificultad para el reconocimiento de la violencia sexual, tanto en hombres como en mujeres (Kim et al, 2019).…”
unclassified